PERANCANGAN SISTEM INFORMASI PEMESANAN LAPANGAN FUTSAL PADA PARUNG FUTSAL - Setiawan, Setiawan (POLITEKNIK LP3I JAKARTA, 2018)
AbstractComputerized system is one of the most important elements in a company, because the computerized system can improve or simplify the process of ordering and service. At this time the ordering process is happening in Parung Futsal, still using manual systems, so in need of a system that can solve the problems such as slow checking data and preparing reports. The author makes a computerized system design from ordering field (booking), indoor soccer field rental transaction process and preparing reports, using a Web program base of PHP as a medium for designing the system. With a system that the authors make is expected to be implemented in Parung Futsal as a tool to solve the constraints of the system that is still manual.Keywords: Computerized System, Online Booking, Footsal Booking.